(3TQM Mce GHf YWGA Gddg (B/ (3TQM GdMce GdYWGFjIs - (3eMeO Hf EHQGgje Hf YHGO GdfaQi GdQfOis ((3aGS s)
(3ChdgG (B:s
(3CeG HYO aEfG deG QCjfG cJGH GdMce GdefShH Edi GdTjN CHj GdaVd JGL GdOjf CNPfG ai hVY JfHjg jchf cGdTQM dHYV eYGfjg GdXGgQI hfMf ai gPg GdcdeGJ GdJi fhQOgG hGdefGMi GdJi fYJHQgG ZjQ eOYjf dTQM cdeGJ Gd eDda hdG Cf eG fPcQg ajg gh Mbj s
(3BNQgG (B:s
(3cja JNai hCfJ GdXGgQ Ce cja JZjH hCfJ GdQbjH GdMGVQ hGddg Gdehab hHg fSJYjf gPG cdg Hjf dG CTcGd ajg hGdMeO ddg hbO JbOe eYfGg ZjQ eGeQI ef cdGe GdeDda QMeg Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdI hGdUaMI GdChdi YdjgG JRhjb HeGA GdPgH s
(3hdaX GdLdGdI ePgH ai LejY GdfSNI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs